Metal-Free Heptazine-Based Porous Polymeric Network as Highly Efficient Catalyst for CO2 Capture and Conversion - Sharma, Neha; Ugale, Bharat; Kumar, Sunil; Kailasam, Kamalakannan (Frontiers in Chemistry, 2021)
The capture and catalytic conversion of CO2 into value-added chemicals is a promising and sustainable approach to tackle the global warming and energy crisis. The nitrogen-rich porous organic polymers are excellent materials for CO2 capture and separation. Herein, we present a nitrogen-rich heptazine-based microporous polymer for the cycloaddition reaction of CO2 with epoxides in the absence of metals and solvents. HMP-TAPA, being rich in the nitrogen site, showed a high CO2 uptake of 106.7 mg/g with an IAST selectivity of 30.79 toward CO2 over N2. Furthermore, HMP-TAPA showed high chemical and water stability without loss of any structural integrity. Besides CO2 sorption, the catalytic activity of HMP-TAPA was checked for the cycloaddition of CO2 and terminal epoxides, resulting in cyclic carbonate with high conversion (98%). They showed remarkable recyclability up to 5 cycles without loss of activity. Overall, this study represents a rare demonstration of the rational design of POPs (HMP-TAPA) for multiple applications.